Impact of Liquidity and Activity Ratios on Stock Price in Indonesia’s Telecom Companies - Suwardi, Rendy Rizky Putra; Siska, Elmira; Sebastian, Dante Rio (Journal of Business and Economics Research (JBE), 2024)
In theory, liquidity and activity ratios serve as current ratioucial indices of a corporation’s financial success and might impact shareholder’s investment decisions. However, academics and practitioners continue to argue the link between these measures on stock price. This study investigates the role of liquidity ratio and activity ratio on stock price of telecommunications firms listed on Indonesia Stock Exchange from 2014 to 2023. This research draws on secondary data from annual reports of telecommunications corporations registered on the Indonesia Stock Exchange (IDX) from 2014 to 2023 and the data is obtained from the official websites of the relevant firms. This research’s population consisted of all telecommunications firms listed on the IDX throughout the relevant timeframe. Purposive sampling was utilized, with 5 firms chosen from a list of 23 existing companies. The acquired data is subsequently analyzed with the IBM SPSS Statistic 25 tool to get the analytical findings. This research concludes liquidity ratio has a negative impact and significance effect on stock price of telecommunications firms listed on Indonesia Stock Exchange from 2014 to 2023 (t-calculated value is - 5,225 is more than the t-table value - 2,01174 and p value 0,000 < 0,05). The activity ratio has a positive impact and significance effect on the stock price of telecommunications firms listed on Indonesia Stock Exchange from 2014 to 2023 (t-calculated value 13,605 is more than t-table value is 2,01174 and p value 0,000 < 0,05).